Characterization of the effect of pomegranate crude extract, and its post-harvesting preservation procedures, on redox tone, cellular growth and metabolic profile of MDA-MB-231 cell line - Aristide Ferrante; Mirko Tamma; Francesca Agriesti; Francesco Tucci; Piervito Lopriore; Maria Luisa Amodio; Giancarlo Colelli; Nazzareno Capitanio; Claudia Piccoli; Consiglia Pacelli (BMC, 2023)
Abstract Background Pomegranate is known for its beneficial properties due to its high content in antioxidants and might constitute a natural option for preventing and treatment of different pathologies including cancer. Since mitochondria are involved in tumorigenesis through ROS production and modulation of oxidative metabolism, we investigated the biological effects of pomegranate on cellular redox state, proliferation and metabolism in the breast cancer cell line MDA-MB-231 (MDA). Methods MDA were treated for 24 h with graded concentration of filtered Pomegranate juice (PJ) and tested for metabolic Flux Analysis with XFe96 Extracellular Flux Analyzer, for proliferation using the xCELLigence System Real-Time Cell Analyzer and for intracellular ROS content by Confocal Microscopy Imaging. Results Cells-treatment with freshly prepared pomegranate juice (PJ) resulted in a significant reduction of the intracellular ROS content already at the lower concentration of PJ tested. Additionally, it enhanced mitochondria respiration, and decreased glycolysis at high concentrations, inhibiting at the same time cell proliferation. As pomegranate is a seasonal fruit, assessment of optimum storage conditions preserving its bio-active properties was investigated. Our results indicated that storage conditions under controlled atmosphere for 30 days was able to enhance mitochondrial respiration at the same extent than freshly extracted PJ. Conversely, freezing procedure, though retaining the antioxidant and cell-growth inhibitory property, elicited an opposite effect on the metabolic profile as compared with fresh extract. Conclusion Overall, the results of our study, on the one hand, confirms the preventive/therapeutic potential of PJ, as well as of its post-harvested processing, for cancer management. On the other hand, it highlights the intrinsic difficulties in attaining mechanistic insights when a multiplicity of effects is elicited by a crude mixture of bio-active compounds.